A new modified Pudendal Thigh Flap of vaginoplasty including reconstruction of vaginal vestibule. Issue 1 (1st January 2017) - Ohmaru, Youkou; Sakata, Kensuke; Hashiguchi, Shin-ichiro; Tanaka, Hiroaki; Rikimaru, Hideaki; Kiyokawa, Kensuke
Abstract: We modified the conventional Pudendal Thigh Flap (PTF) on the vaginoplasty including reconstruction of vaginal vestibule. After the operation, no stenosis of the vaginal vestibule and opening of the vagina was observed. It is believed that our technique is cosmetically and functionally possible and a useful method.